Prarancangan Pabrik Furfural Dari Tandan Kosong Sawit Kapasitas 6000 Ton/Tahun Dengan Disain Alat Utama Evaporator Long Tube Vertical - Pratiwi, Riri Atria; Amraini, Said Zul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Domestic demand for furfural is increasing in line with industrial developments such as the paint, oil, pharmaceutical, plastic and polymer industries. Until now, Indonesia's furfural needs still rely on imports from other countries. Fufural is produced using agricultural waste containing pentosan, such as rice husks, corn cobs, wood, hemp, bagasse, empty fruit bunches and other sources of fiber. Indonesia is a country rich in resources that have the potential to produce raw materials for fufural production, one of which is empty fruit bunches with a pentosan content of 25.90%. The number of empty bunches of waste throughout Indonesia in 2004 had reached 18.2 million tons. . The main design tool is an evaporator (EV-101) which functions to concentrate furfural up to 98% purity. This design was carried out in several steps, namely collecting data sources to support the establishment of the factory, calculating mass and energy balances, calculating heat and mass exchange networks, as well as analyzing and designing furfural evaporators and their supporting accessories. The operating conditions for evaporator 101 (EV-101) are with a feed temperature of 90°C and a pressure of 1 bar and a vapor temperature of 125°C. The type of evaporator used is Long Tube Vertical Evaporator. The evaluation of the economic analysis of the factory design shows that the factory is feasible to build with a Return On Investment (ROI) of 26.65%, Break Event Point (BEP) of 35%, Internal Rate of Return (IRR) of 22.74%, and Payback Period. (PBP) factory is 2.75 years.Keywords: Evaporator, Energy Balance, Furfural, Pentosan.